Geometrijska predstava - Kroulíková, Ludmila (Matematika v šoli, 2016)
This paper discusses the first results of a study conducted at primary and secondary schools in Slovenia. The aim of the study was to research the level of geometric visualisation of students at primary and secondary schools in Slovenia. Students took a test of geometric visualisation in a 2D equilateral triangle.
Keywords: geometric visualisation; geometrijska predstava; matematika; mathematics; osnovna šola; primary school; secondary school; srednja šola; testing; testiranje